2021
DOI: 10.1144/sp510-2020-62
|View full text |Cite
|
Sign up to set email alerts
|

Development and status of active volcano monitoring in China

Abstract: Following decades of geological surveys and studies, 14 active volcanic field have been identified in China. Evidence for Holocene volcanism in several of these areas highlights the need to understand and monitor volcanic hazards in those regions. Six volcano observatories have been established in the past 40 years accordingly. This work reviews China's national capability and history of volcano monitoring, with emphases on the Changbaishan-Tianchi Volcano Observatory and the Tengchong Volcano Observatory. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The post-unrest subsidence and the more recent dynamics of Chagbaishan are poorly known, lacking specific studies and available data. The only available data concern the seismicity (Pan et al, 2021); these data show that after 2002-2005, when an average of 500 events/yr with M Lmax 4.4 was detected, the seismicity sharply decreased to 30 events/year with M Lmax 2.8 between 2010 and 2018.…”
Section: Deformation Pattern and Seismicitymentioning
confidence: 99%
“…The post-unrest subsidence and the more recent dynamics of Chagbaishan are poorly known, lacking specific studies and available data. The only available data concern the seismicity (Pan et al, 2021); these data show that after 2002-2005, when an average of 500 events/yr with M Lmax 4.4 was detected, the seismicity sharply decreased to 30 events/year with M Lmax 2.8 between 2010 and 2018.…”
Section: Deformation Pattern and Seismicitymentioning
confidence: 99%
“…During the volcanic eruption intervals, large amounts of volcanic gases are emitted to the atmosphere because of the continuous heating of the country rock caused by the high-temperature chambers (Guo et al, 2015;Aiuppa et al, 2015;Tassi et al, 2016;Liu et al, 2021). It has been demonstrated that 14 volcanoes in mainland China erupted during the Holocene (wei et al, 1998;Wei et al, 2003;Pan et al, 2021) and are currently in a dormant state. Among the current dormant volcanoes in China, the Changbaishan, Tengchong, and Wudalianchi volcanoes have been investigated by numerous studies to determine their fluid backgrounds (Du et al, 1999;Shangguan et al, 2008;Zhang et al, 2011;2018 ;Liu et al, 2011;Guo et al, 2015;Li, 2015;Zhao, 2012;Wei et al, 2021;Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early Jurassic, affected by the subduction of the Pacific plate and the blocking of the Eurasian plate, a series of NE-oriented faults and volcanic rock belts with different scales have developed. Since the start of the Cenozoic, extensive basaltic magma has violently erupted (Liu, 1987;Liu et al, 2001;Pan et al, 2021). The volcanism in this region is multi-episodic and can be divided into the Pliocene, Pleistocene and Holocene eruption stages.…”
Section: Introductionmentioning
confidence: 99%
“…Various disasters caused by crustal movement have serious adverse effects on national economic development and people's lives and properties [13]. Therefore, effective monitoring of crustal deformation and analysis of its movement laws have great theoretical and practical significance for understanding regional crustal deformation and disaster prevention and mitigation [14].…”
Section: Introductionmentioning
confidence: 99%